Tujuan Bahasa Roh Pada Gereja Mula-Mula Berdasarkan Kisah Para Rasul - Iwan Setiawan; Hilda Naomi; Meny Sulastry; Asmi Wori; Yufen Samgar Feo (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2024)
Tongue is a gift given by God through the power of the Holy Spirit. Tongues come from God and are given to those who truly believe in God. Gifts are complements that God gives freely to people who truly believe so they can serve others for the glory of God, gifts to serve with the aim that others will be saved. True tongues come from the Holy Spirit and are not memorized. All good gifts come from God, when you are filled with the Holy Spirit you must live truly believing in Jesus Christ. The research method used is literature review or library research, namely library searches, utilizing library sources to obtain the data needed by the author in the research. Library research focuses on library collection materials without using field research. The aim of the research is to provide a more comprehensive and biblical understanding of the purpose of tongues according to the Acts of the Apostles. The results of the research obtained regarding the purpose of tongues based on the Acts of the Apostles are that tongues are used to preach the Gospel by reporting the great deeds of God, tongues are used to glorify God, tongues are a sign of baptism and tongues produce life in harmony.